Estimation of Motivation to Achievements of Adults in The Professional Environment - Izabela ZIEBACZ (Communications of International Proceedings, 2021)
Motivation is inextricably linked with the professional activity of a person. It is an individual disposition of an individual, which determines its usefulness for the organization. Many scientific publications point to the important role and importance of human internal motivation, while is noticeable, the lack of methodological publications, translating theoretical concepts into practical organizational activities, enabling the estimation of the motivation for the development of adults in the professional environment. The quantification of the employee's motivation for development would be a useful managerial tool. This article is an attempt to quantify motivation and evaluate its magnitude, using the concept of entropy. The main premise for attempting to define the method of measuring motivation parameters is to improve the management and modeling of adult development processes in the professional environment from the perspective of management activities. Design/methodology: The model presented in the article was tested in two Polish enterprises from the SME sector. The service industry, in terms of motivation to achieve, understood as motivation for self-education and development. The research was carried out in August-October 2020. Findings: The value of the work is an interdisciplinary approach to the issue of motivation. The usage of the estimation of motivation and the information entropy in the analysis of the problem, including the cybernetic approach, allowing to conclude the individual's predispositions. Originality/value: The concept presented in the work can be used as a tool for forecasting and estimating the development of potential employees. The proposed solution may support the human capital management.
Keywords: motivation; estimation; andragogy; human capital management.